DNA double-strand breaks and alkali-labile bonds produced by bleomycin. - Povirk, L F (1977)
Both in linear T2 DNA, analyyzed by velocity sedimentation, and in supercoiled Col EL DNA, analyzed by gel electrophoresis, the number of double-strand breaks produced by bleomycin was directly propotional to the number of single-strand breaks and was far greater than the number expected from random coincidence of single-strand breaks, suggesting that the bleomycin-induced double-strand breaks occur as an independent event. In Col EL DNA, at least twice as many single-strand breaks were found under alkaline assay conditions as were found under neutral conditions, showing the production of alkaline-labile bonds by bleomycin.